Insights into the stability of carotenoids and capsaicinoids in water-based or oil-based chili systems at different processing treatments. (16th April 2021) - Zhang, Rui; Chen, Guangjing; Yang, Bing; Wu, Yun; Du, Muying; Kan, Jianquan
Highlights: The type of chili products affects the stability of carotenoids and capsaicinoids during processing. The stability of carotenoids and capsaicinoids can be significantly improved in an oil-based system. Different processing intensities may have different effects on chili products. It is important to refrigerate and avoid ultraviolet exposure during storage. Abstract: Ultrasonication, microwave, heat, and light treatments, as well as storage conditions, were investigated for their effects on the stability of carotenoids and capsaicinoids in water/oil chili systems. The stability of carotenoids and capsaicinoids were found to vary in response to different processing treatments. Carotenoid and capsaicinoid contents in chili juice (CJ, water system) were increased by low-power ultrasonic and microwave treatments, but decreased by high-power treatments. The thermal stability of carotenoids and capsaicinoids in hot pot bottom (HPB, oil system) were superior to those in CJ. Moreover, ultraviolet light significantly reduced the contents of carotenoids and capsaicinoids in both CJ and HPB. It was also demonstrated that low temperature conditions (4 °C) significantly delayed the degradation of carotenoids and capsaicinoids in chili-based food. In conclusion, our findings suggest that the stability of carotenoids and capsaicinoids can be tuned using different processing and storage techniques appropriate to different systems.